A Prospective Study of I.V. Vinflunine in the Treatment of Patients with Advanced or Metastatic Urothelial Carcinoma after Failure of a Platinum-containing Regimen and Biomarker Correlates - Fatma M.A. Abouelkasem; Tarek Y. Mohamed; Hussein M. Khaled; Ibrahim Malash; Eman Loay (Asian Pacific Journal of Cancer Biology, 2022)
Background: Vinflunine is the only cytotoxic agent that had been tested as a second line therapy in platinum refractory urothelial carcinoma patients in a phase III clinical trial. The aim of our study was to evaluate the efficacy and safety of vinflunine as a second line after failure of platinum containing regimen. Patients and methods: We prospectively included 27 patients of locally advanced or metastatic urothelial cancer who presented to the National Cancer Institute (NCI) of Egypt. The primary objective was to assess the disease control rate. However, the secondary objectives were to assess the progression free survival (PFS) and overall survival (OS). Results: A total of 27 patients were treated at the NCI of Egypt. Median age was 64.1 years (42.3-76.8). Male to female ratio was 26:1. Eastern Cooperative Oncology Group performance status was zero in 2 patients, one in 23 patients while the ECOG PS 2 was in only 2 patients. The vast majority of the patients received 2 cycles (12 patients), one patient received 3 cycles, 5 patients received 4 cycles, and 8 patients received 6 cycles while one patient received 8 cycles. A complete response was observed in one patient, partial response in 9 patients and stable disease in 12 patients and progressive disease in 5 patients with a disease control rate of 81.4%. Median progression free survival (PFS) and overall survival for the entire population were 3.45 months and 3.22 months respectively. Median OS for the responders was 7.24 months. Toxicity was mild, and grade 3-4 adverse events were anemia (11.1%), neutropenic fever (4%), fatigue (14.8%) and constipation (7.4%). Conclusion: Vinflunine is an efficient and tolerable second line treatment in advanced urothelial carcinoma.